IMPROVING STUDENTS' VOCABULARY USING LEXICALLY-BASED LANGUAGE TEACHING TO THE EIGHT YEAR STUDENTS IN SEKOLAH MENENGAH PERTAMA NEGERI (SMP N) I KARTASURA IN 2006/2007 ACADEMIC YEAR - SANTOSO , NOFI FITRI (2007)
This study is aimed at describing three things. They are the implementations of teaching vocabulary using Lexically-based Language Teaching, the teaching result and also the student's response. In achieving the objectives of the research, the writer uses the Classroom Action Research (CAR) which involves four steps, namely planning, implementing, observing and reflecting. The research is held in SMP Negeri 1 Kartasura. The writer takes the eight grade that consists of 41 students as the subject of the study. There are two cycles in this research that each cycle is conducted in three meetings which is in 60'. After concluding and analyzing the data, the writer describes the result of the research as follows: at the first cycle there were 37 students (90,2 %) who increased their vocabulary achievement, 1 student (2,4%) that has decreased her vocabulary improvement, and 3 students (7,3%) who had static achievement in vocabulary improvement. At the second cycle, there were 33 students (80,5%) who increased their vocabulary achievement, 7 students (17,1%) who decreased their vocabulary imorovement, and 1 student (2,4%) who had static achivement in vocabulary improvement. It means the second cycle is more successful than first cycle. Overall, the writer concludes that teaching vocabulary using Lexically- based Language Teaching is appropriate and quite effective for the eight year students of SMP Negeri 1 Kartasura. The students admitted that they loved this technique, they do not feel bored, but more enthusiastic to follow the teaching learning process. The students looked happy and enjoyed the lesson. They also admitted that they become active and full of concentration in the classroom. They were motivated to improve their vocabulary.